Molecular cloning of hypervariable region (HVR II) from cellulose synthase gene in kelampayan (Neolamarckia cadamba) - Sim, Meldon Calvin Wee Yang (Universiti Malaysia Sarawak (UNIMAS), 2011)
Neolamarckia cadamba or locally known as Kelampayan, is one of the light hardwood trees that holds great prospects as a source of raw materials for the paper, pulp, wood and biofuel industries. Sufficient information on cellulose synthase gene, especially the hypervariable region II component involved in wood formation of Kelampayan is imperative for future applications. The aim of this study is to identify and clone the hypervariable region (HVRII) from cellulose synthase gene of N. cadamba. Total RNA was isolated from young leaves and developing xylem tissues of N. cadamba. The cDNA of N. cadamba cellulose synthase HVRII (NcCesAHVRII) region was amplified using reverse transcription-PCR (RT-PCR) approach with forward degenerate primers, HVR2F (5′-TGYTATGTYCAGTTYCCWC-3′) and reverse degenerate primer, HVR2R (5′-GANCCRTARATCCAYCC-3′). NcCesA1HVRII, NcCesA2HVRII and NcCesA3HVRII were successfully sequenced. NcCesA1HVRII and NcCesA3HVRII were clustered to 2 distinct clades implicated with secondary cell wall development. Analysis on NcCesA2HVRII suggests renaming it as NcCslD1HVRII due to high similarity with various plants’ CslD-HVRII. This study will provide an easier and faster access to NcCesAHVRII sequences to further understand the role of NcCesA/NcCslD protein for future application such as in selecting trees with optimal cellulose content required for specific industries.